2018
DOI: 10.1021/acsomega.7b01489
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Dehydrogenation of Propane over a High Surface Area Boron Nitride Catalyst: Exceptional Selectivity for Olefins at High Conversion

Abstract: Developing environment-friendly active and selective catalysts for oxidative dehydrogenation of propane for on-purpose propene synthesis is challenging despite tremendous industrial potential for this reaction. Herein, we report on catalytic activity of high surface area hexagonal boron nitride, toward oxidative dehydrogenation of propane. It shows remarkable selectivity for alkenes (∼70%) at very high conversion (of ∼50%) of propane. Propene and ethene selectivities as high as 53 and 18%, respectively, were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
52
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(57 citation statements)
references
References 30 publications
4
52
0
1
Order By: Relevance
“…We point out that both HOOC and > BOC can either propagate upon reaction with propane or terminate (Reactions (6) and (7)). This leads to ahigher radical quasi steadystate concentration-at ag iven conversion-at higher propane concentrations,l eading to the apparent second order observed for propane (Figure 1).…”
Section: Methodsmentioning
confidence: 95%
See 2 more Smart Citations
“…We point out that both HOOC and > BOC can either propagate upon reaction with propane or terminate (Reactions (6) and (7)). This leads to ahigher radical quasi steadystate concentration-at ag iven conversion-at higher propane concentrations,l eading to the apparent second order observed for propane (Figure 1).…”
Section: Methodsmentioning
confidence: 95%
“…Thea ctivation energy of this water-mediated surface-regeneration process is compatible with experimentally reported apparent activation energies for hBN-catalyzed ODH in the 200-250 kJ mol À1 range. [6,12,27] Therefore,w eh ypothesize that this water-mediated site regeneration is the rate-limiting reaction in the overall ODH reaction, and not the H abstraction from the alkane substrate as hypothesized for vanadium. [20,28] Summarizing the findings from our computational studies, we identified two radical initiation mechanisms Reactions (2) and (3), and Reaction (4):…”
Section: Methodsmentioning
confidence: 96%
See 1 more Smart Citation
“…Su等 [13] 制备了高比表氮化硼纳米片 (BN nanosheets)应用于乙烷氧化脱氢反应中, 得到了 优于商业h-BN的活性和选择性. Eswaramoorthy等 [14] 也报道高比表面的h-BN可以提高丙烷氧化脱氢反应 的性能, 在丙烷的转化率为52%时, 丙烯和乙烯的选择 性分别为53%和18%. 但催化剂只能维持5 h的稳定性, 随后出现失活, 通过加入氨气则可以再生催化剂活性, 并通过氨气共进料可以实现100 h的催化剂稳定性.…”
Section: 择性仍高达90% 且催化剂可以在590°c条件下保持unclassified
“…In recent years, considerable research efforts have been focused on the oxidative dehydrogenation of propane to propylene . Propylene is an important chemical feedstock that is in demand mainly for the production of polypropylene, acrylic acid acrylonitrile, and iso‐propanol.…”
Section: Introductionmentioning
confidence: 99%